2017
DOI: 10.1177/0091415017727211
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sex, Socioeconomic Status, and Emotional Support in Predicting Aging Perception Among Older Adults

Abstract: Self-perception is found to be a central predictive factor in experiencing successful aging. The aim of this study was to explore the role of sex, socioeconomic status, and emotional support in elders' aging perception. A cross-sectional design was used with 300 older aged participants recruited from 23 clinics and health centers in Qazvin, Iran. Data were collected included questions to elicit demographic information and Barker's aging perception questionnaire. Exploratory multiple linear regression showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
(25 reference statements)
2
4
1
Order By: Relevance
“…In this sense, in our study in the measurement of the self-perception of the old age before the workshop, we observed a better perception of the old age in the group with higher schooling in comparison with the low schooling group, although after the workshop both groups showed better perception of old age. These findings are in agreement with other studies [ 19 , 20 ], although it has also been found that education does not influence the self-perception of aging [ 21 ], which suggests that, besides the years of schooling, social representations of old age are a determining factor [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, in our study in the measurement of the self-perception of the old age before the workshop, we observed a better perception of the old age in the group with higher schooling in comparison with the low schooling group, although after the workshop both groups showed better perception of old age. These findings are in agreement with other studies [ 19 , 20 ], although it has also been found that education does not influence the self-perception of aging [ 21 ], which suggests that, besides the years of schooling, social representations of old age are a determining factor [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Adult children, living expenses, and costs (e.g., children’s education, treating chronic diseases associated with aging) can contribute to the financial distress of older people (Saberian, Hajiaghajani, & Gorbani, 2003). Despite the weak correlation of the present findings, evidence from the broader literature supports the notion that family members who provide emotional support and financial support to their older relatives can have a positive impact on AP in the elderly (Yaghoobzadeh et al, 2017). Future research using a larger sample size may produce a stronger correlation between financial support and AP as found in other studies with much larger participant groups.…”
Section: Discussioncontrasting
confidence: 43%
“…There is a growing body of literature that recognises the importance of successful and positive aging to cater to the growing aging population experienced by most countries around the world. [1][2][3][4] According to estimates, older people 65 years and over have an annual global growth rate of 2.5% per year. 5 About two thirds of the world's older people now live in developing countries such as Iran.…”
Section: Introductionmentioning
confidence: 99%